LOCAL TRADITIONS OF THE COMMUNITY IN NGRANDU VILLAGE, PONOROGO REGENCY INDONESIA - Agus Rahmat Mahmudi; Eka Yudha Wibowo; Nuraeni Martha (SOSIOEDUKASI, 2025)
This study discusses the local traditions of the community in Ngrandu Village, Ponorogo Regency. The purpose of this research is to find out what traditions exist in Ngrandu Village and find out what values are contained in the traditions in Ngrandu Village, Ponorogo Regency. The method used in this study is qualitative ethnography. Data collection techniques in this study include: observation, interviews, and document review. The data analysis techniques in this study include: data reduction, data presentation, and conclusion drawn. The result of this research is that Ngrandu Village in Ponorogo Regency has three traditions that are still preserved by the community, namely the kenduri/selametan tradition, the harvest tradition, and the wedding tradition. The three traditions have their own philosophical values. So that local traditions need to be applied and preserved by the younger generation because they have various meaningful moral and philosophical values.